Vascular endothelial growth factor inhibitors for retinopathy of prematurity - O.V. Zhukova; I.A. Mal’tseva; A.V. Zolotarev (РМЖ "Клиническая офтальмология")
O.V. Zhukova1, I.A. Mal’tseva2, A.V. Zolotarev1,2 1Samara State Medical University, Samara, Russian Federation 2T.I. Eroshevskiy Samara Regional Clinical Ophthalmological Hospital, Samara, Russian Federation The article addresses current treatment modalities for threshold retinopathy of prematurity (ROP) and aggressive posterior retinopathy of prematurity (APROP), in particular, intravitreal administration of vascular endothelial growth factor (VEGF) inhibitors. The results of multicenter clinical trials evaluating pegaptanib, bevacizumab, and ranibizumab are discussed. The clinical effect of intravitreal anti-VEGF drugs was compared to the efficacy of laser retinal photocoagulation. In children with ROP, anti-VEGF drugs are equal or even superior to the conventional laser retinal photocoagulation in terms of clinical efficacy. No negative effects of anti-VEGF drugs on ocular tissues or vasculature development in premature children were demonstrated. Moreover, several studies show the potential efficacy of intravitreal anti-VEGF drugs plus avascular zone photocoagulation for APROP. Finally, our experience with intravitreal ranibizumab for threshold ROP and plus d isease in a patient who was followed-up for subsequent 9 years is described. Keywords: retinopathy of prematurity, plus disease, aggressive posterior retinopathy of prematurity, anti-VEGF drugs, ranibizumab. For citation: Zhukova O.V., Mal’tseva I.A., Zolotarev A.V. Vascular endothelial growth factor inhibitors for retinopathy of prematurity. Russian Journal of Clinical Ophthalmology. 2020;20(4):216–220. DOI: 10.32364/2311-7729-2020-20-4-216-220.